Pengaruh Ekstrinsik Reward dan Intrinsik Reward Terhadap Employee Performance: Telaah Pada PT. XYZ - Raymond Januar; Dewi Wahyu Handayani (Universitas Multimedia Nusantara, 2015)
This research is to measure the influence of extrinsic reward and intrinsic reward againts employee performance. This research was performed in PT XYZ located in BSD city, Tangerang Selatan. Primary data was used for the collection of data. The data was obtained from 60 respondents, who are employees and permanent teachers of PT XYZ. The case study has been carried out by using a quantitative approach. The results are extrinsic reward and intrinsic reward does have a positive relationship to employee performance, but the two must be performed together. Keywords: Reward, Extrinsic Reward, Intrinsic Reward, Employee Performance